Probing Systematic Bias in Low-redshift Type Ia Supernova Measurements by Cross Analyzing Surface Brightness and Hubble Residuals. (28th January 2021) - Solak, H.; Kessler, R.; Jones, D. O.
Abstract: For low-redshift ( z < 0.1) SN Ia samples used in several cosmological analyses over the past decade, we probe for systematic bias by looking for correlations between surface brightness (SB) measurements and Hubble residuals (HR). For 292 SNe Ia, we measure SB at the location of the SN Ia from publicly available Pan-STARRS (PS1) images. The Hubble residuals are from two recent measurements with low- z SNe Ia that overlap the PS1 footprint: (1) the DES 3 yr cosmology analysis, with 120 overlapping low- z SNe Ia from the Harvard-Smithsonian Center for Astrophysics surveys and Carnegie Supernova Project, and (2) the PS1 single-telescope analysis, with 172 overlapping low- z SNe Ia from the Foundation Supernova Survey. This study is motivated by previous reports of anomalous inefficiencies and flux scatter for transients on bright galaxies. We compare HR distributions of the bright and faint halves of the SB distribution: the mean HR values differ by Δ HR ̄ = 0.031 ± 0.018, consistent with no difference at the 2 σ level. We also perform a Kolmogorov–Smirnov (KS) test for the bright and faint half HR distributions, and conclude that the two distributions are statistically consistent with a KS p -value of 0.07. However, if future studies with larger data sets find Δ HR ̄ ∼ 0.03 with high significance, this difference would be a leading systematic uncertainty in measurements of the dark energy equation of state, w .